Pengaruh Konsentrasi Asap Cair Terhadap Mutu, Total Bakteri, dan Waktu Simpan Ikan Cakalang (Katsuwonus pelamis) Asap: Effect of Liquid Smoke Concentration on Quality, Total Bacteria, and Shelf Life of Smoked Skipjack Fish (Katsuwonus pelamis) - Angria Deswika Malambu; Syaiful Bahri; Hardi Ys.; Prismawiryanti; Abd. Rahman Razak (KOVALEN: Jurnal Riset Kimia, 2021)
Liquid smoke contains acid, carbonyl, and phenolic compounds, so it is very appropriate to be used as a preservative. Traditional smoking can be replaced with liquid smoke because it is safer and more practical. The study of the use of coconut shell liquid smoke has been used in skipjack fish to determine the effect of liquid smoke concentration and storage time on dissolved protein content and total bacteria in smoked fish. The quality of smoked fish was determined by two treatments, namely the variation in the concentration of liquid smoke (2, 3, 4, and 5%) and storage time (2, 4, 6, 8, and 10 days). The results showed that the best concentration of liquid smoke to produce smoked skipjack fish is 3% with a water content of 62.41% and dissolved protein content of 17.58%. The maximum storage time of smoked skipjack tuna is 6 days with a total plate count (TPC) value or total bacteria 1.8 x 105.